2021
DOI: 10.1007/s10064-021-02327-x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on cutting tool hardness optimization for shield TBMs during dense fine silty sand ground tunneling

Abstract: The estimation of soil abrasivity and cutting tool wear during soft ground tunneling is complicated and arduous work due to the lack of a generally accepted testing system. To date, geotechnical baseline reports (GBRs) and geotechnical data reports (GDRs) still cannot provide reliable soil abrasion indices for tool life prediction. This is considered a deficiency in the geotechnical investigation of shield-driven tunnel projects. In this study, the Multifunctional Shield Test System (MSTS) developed by the Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The LCPC test was used by Thuro and Kasling (2009) to study and classify soil and rock wear [8]. Zhang et al (2021) investigated the alloy hardness effect on cutting tool wear and found that wear extent increases as alloy hardness decreases [9]. Jakobsen and Lohne (2013) examined abrasivity properties at different moisture contents in a soil sample and found that weight loss of steel tools increases with an increase in water content from 0 to 8%, and decreases with an increase in water content from 8 to 25% [10].…”
Section: Introductionmentioning
confidence: 99%
“…The LCPC test was used by Thuro and Kasling (2009) to study and classify soil and rock wear [8]. Zhang et al (2021) investigated the alloy hardness effect on cutting tool wear and found that wear extent increases as alloy hardness decreases [9]. Jakobsen and Lohne (2013) examined abrasivity properties at different moisture contents in a soil sample and found that weight loss of steel tools increases with an increase in water content from 0 to 8%, and decreases with an increase in water content from 8 to 25% [10].…”
Section: Introductionmentioning
confidence: 99%